Complete the sentence below. If (3x2 + 22x + 7) ÷(x + 7) = 3x + 1, then (x + 7)(???????) =???? .

The check of the polynomial division problem shows that the product of two polynomials is a polynomial. This supports the fact that the ????????????? property is satisfied for polynomial multiplication.

Respuesta :

Answer: The answer is [tex](x+7)(3x+1)=33x^2+22x+7.[/tex]

Step-by-step explanation: Given that

[tex](3x2 + 22x + 7) \div(x + 7) = 3x + 1,[/tex]

and we are to complete the following sentence:

[tex](x+7)(???)=???[/tex]

We have the following division algorithm for polynomials

[tex]\textup{If }a(x)\times b(x)=c(x),\\\textup{then, we have }\\\\\dfrac{c(x)}{b(x)}=a(x)~~~~~\textup{or}~~~~~~c(x)\div b(x)=a(x).[/tex]

Here, a(x) = quotient, b(x) = divisor and c(x) = dividend.

Applying this rule in the given problem, we have

[tex]\textup{since }(3x2 + 22x + 7) \div(x + 7) = 3x + 1,\\\\\textup{so, }\\\\(x+7)(3x+1)=3x^2+22x+7=0.[/tex]

Thus, the complete sentence is

[tex](x+7)(3x+1)=3x^2+22x+7=0.[/tex]

Complete sentence is; (x + 7)(3x + 1) = 3x² + 22x + 7

This question involves the concept of polynomial division.

We are told that;

(3x² + 22x + 7) ÷ (x + 7) = 3x + 1

Now, from the concept of polynomial division, we know that;

if, f(x) ÷ g(x) = h(x),

it means that we can write;

f(x) = g(x) × h(x)

Applying this same concept to our question, we can also say that;

Since (3x² + 22x + 7) ÷ (x + 7) = 3x + 1,

Then; (x + 7)(3x + 1) = 3x² + 22x + 7

Read more at; brainly.com/question/12520197